2009
DOI: 10.1093/humrep/dep069
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine concentrations in follicular fluid are associated with poor oocyte and embryo qualities in polycystic ovary syndrome patients undergoing assisted reproduction

Abstract: Concentrations of Hcy in follicular fluid on the dOPU may be a useful marker for fertilization rate, and oocyte and embryo quality in PCOS patients undergoing assisted reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
113
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 56 publications
2
113
1
3
Order By: Relevance
“…The presence of Hcy in follicular fluid was demonstrated already in 1993 [20]. More recently, new studies assessed the concentration of Hcy in follicular fluid [17,18] and our levels are a little lower than the published with mean ± SD value of 6.0 ± 0.9 μmol/l and median of 6.1 μmol/l in follicles without oocyte and 5.2 ± 0.8 μmol/l and median of 5.2 μmol/l in follicles containing the oocyte. It was also reported that low follicular fluid Hcy concentration is associated with a higher degree of the oocyte maturation [20] and that there is a significant association between follicular fluid Hcy levels and the grade of oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of Hcy in follicular fluid was demonstrated already in 1993 [20]. More recently, new studies assessed the concentration of Hcy in follicular fluid [17,18] and our levels are a little lower than the published with mean ± SD value of 6.0 ± 0.9 μmol/l and median of 6.1 μmol/l in follicles without oocyte and 5.2 ± 0.8 μmol/l and median of 5.2 μmol/l in follicles containing the oocyte. It was also reported that low follicular fluid Hcy concentration is associated with a higher degree of the oocyte maturation [20] and that there is a significant association between follicular fluid Hcy levels and the grade of oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that low follicular fluid Hcy concentration is associated with a higher degree of the oocyte maturation [20] and that there is a significant association between follicular fluid Hcy levels and the grade of oocytes. High follicular fluid Hcy levels are negatively correlated with oocyte fertilization and the quality of embryo, which indicates that follicular fluid Hcy may play an important role in the development of oocytes and fertilization [18]. Hcy is a well-known inhibitor of methylation reactions and this could explain why high Hcy levels negatively affect methylations and consequently the oocyte and embryo development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 Increased plasma and follicular homocysteine levels negatively correlate with oocyte maturation leading to a number of development defects of the oocyte that impede fertilization and/or the reproductive outcome in polycystic ovarian syndrome (PCOS) patients undergoing assisted reproduction. 16,17 Hence, this study was planned to evaluate serum homocysteine levels, prevalence of MTHFR polymorphism in infertile women and to evaluate the role of hyperhomocysteinemia and MTHFR 677 C>T mutation in female infertility.…”
Section: Introductionmentioning
confidence: 99%